(3GdHGH aj eYQag GdCfSGHs - (3CHh GdMSf CMeO Hf eMeO Hf EHQGgje GdCTYQj GdfSGHg Gdjefjs
(3ChdgG (B:s
(3HYO GdHSedI hHYO agPG eNJUQ ai Yde GdfSH hbHGFd GdYQH LYdJg PQjYI ai GdGNJUGQ hSHjd ai GdEbJUGQ s
(3BNQgG (B:s
(3hbO bjd Gf NhdGf Gh dGOGNQS YJQjS SeGg s
(3ai GdeNWhWI GddHGH hGdUhGH eG CKHJfG heYfGg GdeONd ceG jPcQ ai GdebOegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B42 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs